Effective regulation in emerging market banking industries: twin-peaks versus market discipline plank of basel accord - Godspower-Akpomiemie, Euphemia (My University, 2018)
This study examines the efficacy and performance effects of two major ideas in financial regulatory innovation: the market discipline principle of Basel II Capital Accord, and the twin-peaks model of financial regulation. These two regulation ideas are examined for their differential effects on emerging market versus developed market banks. Generalized Method of Moments (GMM) estimation and logistic regression techniques are the main tools of analysis in the study, as well as difference-in-differences (DID) technique that is used for robustness checks. Market discipline is found to exist in the banking industries of our sample countries, and bank performance and stability are responsive to the implementation of the market discipline principle. Market discipline affects the two distinct economies of emerging and developed economies differently, with there being higher levels of market discipline from both internally and externally originated market discipline in developed market, than in emerging market economies. The twin-peaks financial regulatory model is found to positively affect banks, with significant improvement on bank performance and stability that is attributable to adoption of twin-peak features by emerging market countries. Interestingly, it is found that market discipline and twin-peaks regulatory model are complements rather than substitutes in the emerging economies’ financial regulatory space. Based on the above findings and various other policy implications of the study, we recommend that countries which have already implemented Basel II’s market discipline principle should also endeavor to implement twin-peaks financial regulatory model as well, for enhanced bank performance. Compliance with financial regulatory policies, in general, is also found to be value-enhancing for national financial markets; therefore, we additionally recommend that countries, of both emerging and developed economy levels, should endeavor to comply with required financial regulatory policies that are already in place.
Doctoral Thesis Submitted in Fulfilment of the Requirements for the Award of Doctor of Philosophy in Finance The Graduate School of Business Administration, Wits Business School University of the Witwatersrand Johannesburg South Africa, January 2018
Keywords: Financial institutions; International finance--Law and legislation.